PENGARUH PROFESIONALISME AUDITOR, PENGETAHUAN MENDETEKSI KEKELIRUAN, PENGALAMAN AUDITOR DAN ETIKA PROFESI TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS AKUNTAN PUBLIK (Studi Empiris KAP di Pekanbaru, Medan dan Padang) - Dirangga Madali; Amir Hasan; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This Study aims to examine the effect of Professionalism of auditors, the knowledge to detect errors, auditors experience and professional ethics of the materiallity level considerations of Public Accountant. The population in this study is Auditors who worked in public accounting firms in Pekanbaru City, Medan and Padang.The sampling technique using Purpossive sampling. The data of this research using primary data directly throught a questionnaires and analyzed using SPSS 20.0. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. The result of this study with constant point (11.917) showed that Professionalism (0,141), Knowledge (0,298), Experience (0.729) and Professional Ethics (0,143) have effect on the Materiality Level Considerations of Public Accountant.Keywords : Professionalism, Knowledge, Experience, Ethics and Materiality.